The birthday girl : a novel - De la Cruz, Melissa, 1971- (Dutton, 2019)
Ellie de Florent-Stinson is celebrating her fortieth birthday with a grand celebration in her fabulous house in Palm Springs. At forty, it appears Ellie has everything she ever wanted: a handsome husband; an accomplished, college-age stepdaughter; a beautiful ten-year-old girl; two adorable and rambunctious six-year-old twin boys; lush, well-appointed homes in Los Angeles, Park City, and Palm Springs; a thriving career as a well-known fashion designer of casual women's wear; and a glamorous circle of friends. Except everything is not quite as perfect as it looks on the outside--Ellie is keeping many secrets. This isn't the first birthday celebration that hasn't gone as planned. There's a certain sixteenth birthday that she's tried hard to forget. But hiding the skeletons of her past comes at a cost, and all of Ellie's secrets come to light on the night of her fabulous birthday party in the desert--where everyone who matters in her life shows up, invited or not. Old and new, friends and frenemies, stepdaughters and business partners, ex-wives and ex-husbands congregate, and the glittering facade of her life crumbles in one eventful night. Beautifully paced and full of surprises, The Birthday Girl is an enthralling tale of a life lived in shadow, and its unavoidable consequences.